Biological aspects of Orius insidiosus (Say) feeding on eggs of Plutella xylostella (Linnaeus) and Anagasta kuehniella (Zeller). - Brito, J.P.; Vacari, A.M.; Thuler, R.T.; De Bortoli, S.A. (My University, 2009)
The objective of this work was to evaluate the biology of Orius insidiosus fed on eggs of Plutella xylostella and Anagasta kuehniella. The eggs used were obtained from the Laboratorio de Biologia e Criacao de Insetos, Departamento de Fitossanidade, FCAV/UNESP. The experiment was carried out with a total of 50 12-to-24-hour-old O. insidiosus nymphs, 1 per Petri dish (50 replications). P. xylostella or A. kuehniella eggs were places into each Petri dish daily, along with a small cotton pad moistened with distilled water. The evaluations were carried out daily. The adults were separated in couples, and placed in Petri dishes. The following biological aspects were evaluated: duration, survival rate and consumption of the nymph instars and of the nymph period; longevity of males and females; consumption per day and adult longevity; eggs per day; female fecundity; egg viability; embryonic period; preoviposition period, oviposition period, post-oviposition period. The fertility life table parameters were also evaluated. The predator O. insidiosus did not present significant differences for its biological characteristics, when feeding on P. xylostella and A. kuehniella eggs, however it showed improved fertility life table parameters when fedo n eggs of P. xylostella, suggesting the possibility of using these eggs in the mass rearing of this insect.